Murder, She Wrote : First Season Disc 3 Episodes 6-13 - Fischer, Peter S.; Ron Masak; Tom Bosley; William Windom; Angela Lansbury; Levinson, Richard, 1934-1987; Link, William, 1933- (USA Corymore Productions, 1984)
Former substitute English teacher and famed mystery writer Jessica Fletcher has a gift for solving mysteries. You see, it seems murder follows her around, whether it be to the houses of her seemingly endless number of friends, nieces, and nephews or right in her hometown of Cabot Cove, Maine. Jessica is sometimes assisted by her friend Dr. Seth Hazelet or the local sheriff, Amos Tupper (later Sheriff Metsger). Sometimes, early in the series, Jessica would only narrate the episode, which would be a dramatization of one of her novels. In later seasons, Jessica moved to New York City to be closer to her publisher and also closer to crime.
Mystery writer finds herself investigating murders that occur around her.
Language : English Subtitles : English
Keywords: Comedy; Crime; Mystery -- Tv Series; Drama